RESEARCH OF THE PSYCHOLOGICAL CAUSES OF DISADAPTATION OF THE CHILDREN OF THE EARLY AGE TO THE CONDITIONS OF THE PRESCHOOL ORGANIZATIONS - Килыбаева, Гульнур; Бекмагамбетова, Роза; Есполова, Гулден (Pedagogy and Psychology, 2023)
The article is devoted to the study of the problem of maladaptation of young children to the conditions of a kindergarten, since a child's abrupt transition to a new social environment often causes him emotional disorders or a delay in the pace of psychophysical development. In this regard, the purpose of the study was: to study the psychological causes of maladaptation of young children to the conditions of preschool educational institutions. As indicators of the psychological causes of maladaptation, the following were determined: the level of development of cognitive processes, the degree of severity of individual psychological characteristics of a person, and interpersonal relationships. To achieve the goal of the study, the following methods were used: analysis of scientific literature on the research problem, testing, peer review, mathematical methods of statistical processing (Student's t-test). The results of the study showed that difficulties in adaptation in a young child are not caused by one psychological reason, but are accompanied by interrelated and interdependent factors.